Homocysteine metabolism enzyme gene polymorphisms in non-syndromic Malaysian congenital heart disease patients - Mohamad, Nur Afiqah (2013)
Congenital heart disease (CHD) mainly is caused by the incomplete development of the heart during the first 6 weeks of pregnancy. Chromosomal and genetic abnormalities in the child and high levels of homocysteine in the blood are some of the risk factors related to CHD. Several studies in various populations have been done to determine the candidate genes in the predisposition to CHD with contradictory results, but there have been no studies that had been found in Malaysian CHD patients. Hence, this study was conducted to determine the allelic and genotypic analysis of the polymorphisms in candidate genes of the homocysteine enzymes which are the Methylenetetrahydrofolate Reductase (MTHFR), Cystathionine-b-synthase (CBS), Methionine Synthase (MTR) and Methionine Synthase Reductase (MTRR) genes. We conducted an unmatched cross-sectional study between CHD patients and healthy subjects to determine the association of these polymorphisms with CHD. Based on the inclusion and exclusion criteria, buccal or blood samples were collected from 150 Malaysian non-syndromic CHD patients and 150 samples from healthy subjects as controls with no matching of age, genders and race between cases and controls. Genomic DNA was extracted from the samples using commercially available kits and the genotyping analysis for C677T MTHFR, A1298C MTHFR, A66G MTRR, A2756G MTR and 844ins68 CBS gene polymorphisms are analyzed using the PCR-RFLP analysis. This study showed that there was a significant difference observed in the MTHFR A1298C gene polymorphisms between cases and controls with a significance value of P=0.008. When compared between genders and races, there was also a significant difference observed between males (P=0.003) and females (P=0.037) and among the Malay ethnics (P=0.023) of both CHD and control groups. On the other hand, no significant difference was observed for genotype frequencies between cases and controls of the MTHFR C677T, MTRR A66G, MTR A2756G and CBS 844ins68 gene polymorphism. The association of MTHFR A1298C with the development of CHD in this study emphasis the role of MTHFR gene in the pathogenesis of non-syndromic CHD. The other selected polymorphisms of MTHFR, MTRR, MTR And CBS gene were not associated with the development of CHD in Malaysian subjects. However, investigating these genes in a bigger samples size for different variants might reveal an association of those genes polymorphisms with the development of CHD in Malaysian subjects.